Large Dumbbell Shaped Vesicovaginal Calculus Managed with Holmium Laser Cystolithotripsy Followed by Staged Repair of Vesicovaginal Fistula - Sawant, Ajit (J Clin Diagn Res, 2016)
Complicated Vesicovaginal Fistulae (VVF) is prevalent in developing countries following obstetric injury. We report a rare case of a large dumbbell shaped vesicovaginal calculus measuring 7x 4.6cm in a patient with recurrent, complicated VVF managed successfully in two stages 6 weeks apart. Holmium laser (30 Watt) cystolithotripsy was used to break the vesical portion of the stone at the waist of the dumbbell, followed by delivery of vaginal part of the stone. Trans-abdominal VVF repair (O’Connor method) with omental interposition flap with right side ureteric reimplant was done after six weeks. Our case was unique because of occurrence of a larger sized fistula after a gynaecological surgery. She had developed larger stone (weight more than190gm- vaginal component) into the fistula tract. Also she had undergone multiple failed VVF repair attempts before. Use of holmium laser energy to break the stone was unique which minimized the morbidity of the first procedure leading to early recovery followed by staged repair of fistula after six weeks.